TINGKAT ADOPSI DAN DAMPAK PENGGUNAAN MESIN PANEN PADI DI DESA BELO KECAMATAN GANRA KABUPATEN SOPPENG - Sri Ramdanah; Asriyanti Syarif; Rasdiana Mudatsir (Institute of Computer Science (IOCS), 2023)
This study aims to analyze he adoption of rice harvesting machine technology and the economic and social impact of using harvesting machines in Belo Village, Ganra District, Soppeng Regency. Determination of the population and sample in this research was carried out using a random sampling technique with a total sample of 34 people. while the data analysis technique was descriptive qualitative analysis and used Spearman rank correlation. The results showed that the level of technology adoption was in the high category with an average of 2.58. This means that farmers have high awareness, interest, evaluation, trial and acceptance by adopting agricultural technology, especially rice harvesting machines (combine harvesters). The impact of using harvesting machines economically helped farmers minimize harvesting costs and harvesting can be done efficiently and effectively, it also reduced the farmers' expenses due to the lack of labor needed and resolved the delays in harvesting. Socially affects the relations between farmers and farm laborers, but socially affects decreasing the relationship between farmers and other farmers and farm workers because the cooperation system has been replaced by the presence of technology.